Feedback of personal retinal images appears to have a motivational impact in people with non‐proliferative diabetic retinopathy and suboptimal HbA1c: findings of a pilot study. Issue 9 (19th April 2013) - Rees, G.; Lamoureux, E. L.; Nicolaou, T. E.; Hodgson, L. A. B.; Weinman, J.; Speight, J.
Abstract Aim To conduct a pilot study to explore the potential impact of visual feedback of personal retinal images on diabetes outcomes. Methods Twenty‐five participants with non‐proliferative diabetic retinopathy and suboptimal HbA1c (> 53 mmol/mol; > 7%) were randomized to receive visual feedback of their own retinal images or to a control group. At baseline and 3‐month follow‐up, HbA1c, standard measures of beliefs, diabetes‐related distress and self‐care activities were assessed. Results In unadjusted models, relative to controls, the intervention group showed significantly greater improvement in HbA1c at 3‐month follow‐up (–0.6% vs. +0.3%, P < 0.01), as well as enhanced motivation to improve blood glucose management (P < 0.05). Conclusions This small pilot study provides preliminary evidence that visual feedback of personal retinal images may offer a practical educational strategy for clinicians in eye care services to improve diabetes outcomes in non‐target compliant patients. A fully powered randomized controlled trial is required to confirm these findings and determine the optimal use of feedback to produce sustained effects.